Nothing at all - Gág, Wanda, 1893-1946 (Fesler-Lampert Minnesota heritage book series., 2004)
Left alone when his two visible brothers are chosen as pets by a little girl and boy, an invisible puppy tries to find a way to become a dog that everyone can see and love.